2018
DOI: 10.1111/cpr.12444
|View full text |Cite
|
Sign up to set email alerts
|

Loss of PPM1F expression predicts tumour recurrence and is negatively regulated by miR‐590‐3p in gastric cancer

Abstract: PPM1F may function as a suppressive factor and is negatively regulated by miR-590 in GC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 31 publications
1
27
0
Order By: Relevance
“…PPM1F, expressed in a variety of tumor cell lines, facilitates cell motility and invasiveness [ 4 ] and breast carcinogenesis by inactivating p53 signaling [ 5 ], promotes tumor metastasis via MAPK signaling and exosome cytokine secretion [ 6 ], and represses cell apoptosis through the TAK1-IKK-NF-κB pathway [ 7 ]. However, our previous study showed that PPM1F is downregulated in gastric cancer (GC), and low expression of PPM1F is associated with poor survival in patients with GC [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…PPM1F, expressed in a variety of tumor cell lines, facilitates cell motility and invasiveness [ 4 ] and breast carcinogenesis by inactivating p53 signaling [ 5 ], promotes tumor metastasis via MAPK signaling and exosome cytokine secretion [ 6 ], and represses cell apoptosis through the TAK1-IKK-NF-κB pathway [ 7 ]. However, our previous study showed that PPM1F is downregulated in gastric cancer (GC), and low expression of PPM1F is associated with poor survival in patients with GC [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, the function of miR-590-3p in different tumors remains controversial. MiR-590-3p relatively high expressed in gastric carcinoma (GC) samples and was associated with tumor relapse in GC patients by direct regulating PPM1F [16] . MiR-590-3p motivated colon cancer cell growth and metastasis via Wnt/β-catenin signaling pathway and Hippo pathway [6; 17] and enhanced ovarian cancer proliferation and metastasis via targeting Cyclin G2, FOXA2 and FOXO3 [18; 19] .…”
Section: Disscussionmentioning
confidence: 99%
“…Every effort has been made to improve the pathogenesis and therapeutic strategies of GC [2], such as eradication of Helicobacter pylori [3], but GC is generally diagnosed at an advanced stage and its prognosis is poor due to tumor invasiveness [4]. Substantial evidence shows that deregulated expression of non-coding RNAs (ncRNAs) is linked to the progression of GC [5,6]. Thus, it is indispensable to identify novel biomarkers for early detection of GC.…”
Section: Introductionmentioning
confidence: 99%